The Response of Jabon Seeds Germination (Anthocephalus cadamba (Roxb.)Miq.) against the Duration of Combustion and Illumination - Vauzia Vauzia; Eliza Gusmira (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2018)
The purpose of this research is to know the response of jabon seeds germination against combustion and ilumination. The design that is used is RAL with 2 factors in it. The first is from the duration of combustion and the second is from the illumination treatment. Based on the design, there are 10 combination of treatments and every treatment will be done 3 times so there will be 30 experiments for the total. The parameter that is observed is the duration of jabon seed germinating and the length of jabon’s root. The result of this research showed that the combustion factor, the illumination factor, and the interaction between combustion and illumination is mattered to the duration of jabon seed germinating. While the length of jabon’s root depends with the combustion factor and the illumination factor. The interaction between the duration of combustion and illumination will not affect the length of jabon’s root at all.